Hīkoi: Forty Years of Māori Protest - Harris, Aroha (Huia Publishers, 2004)
Hikoi is a photographic history of Maori protest - the public face, the rationale, the organisation and the toil behind the scenes. The images and accompanying text tell the story of protests that were turning points: Springbok Tour demonstrations and Raglan, Bastion Point and Waitangi, the Tent Embassy at Parliament in 1972, the Maori Land March 1975 and Hikoi 2004. Hikoi gives a glimpse of some of the hard-earned fruits of those protests: some traditional lands returned to Maori, the Waitangi Tribunal established, te reo Maori made an official language, Maori medium education and Maori media.
Keywords: hikoi; history; protest; rangatiratanga